Superconducting, Topological, and Transport Properties of Kagome Metals CsTi3Bi5 and RbTi3Bi5 - Yi, Xin-Wei; Liao, Zheng-Wei; You, Jing-Yang; Gu, Bo; Su, Gang (Research (Washington), 2023)
The recently discovered ATi3Bi5 (A=Cs, Rb) exhibit intriguing quantum phenomena including superconductivity, electronic nematicity, and abundant topological states. ATi3Bi5 present promising platforms for studying kagome superconductivity, band topology, and charge orders in parallel with AV3Sb5. In this work, we comprehensively analyze various properties of ATi3Bi5 covering superconductivity under pressure and doping, band topology under pressure, thermal conductivity, heat capacity, electrical resistance, and spin Hall conductivity (SHC) using first-principles calculations. Calculated superconducting transition temperature (Tc) of CsTi3Bi5 and RbTi3Bi5 at ambient pressure are about 1.85 and 1.92 K. When subject to pressure, Tc of CsTi3Bi5 exhibits a special valley and dome shape, which arises from quasi-two-dimensional compression to three-dimensional isotropic compression within the context of an overall decreasing trend. Furthermore, Tc of RbTi3Bi5 can be effectively enhanced up to 3.09 K by tuning the kagome van Hove singularities (VHSs) and flat band through doping. Pressures can also induce abundant topological surface states at the Fermi energy (EF) and tune VHSs across EF. Additionally, our transport calculations are in excellent agreement with recent experiments, confirming the absence of charge density wave. Notably, SHC of CsTi3Bi5 can reach up to 226ℏ ·(e· Ω ·cm)-1 at EF. Our work provides a timely and detailed analysis of the rich physical properties for ATi3Bi5, offering valuable insights for further experimental verifications and investigations in this field.The recently discovered ATi3Bi5 (A=Cs, Rb) exhibit intriguing quantum phenomena including superconductivity, electronic nematicity, and abundant topological states. ATi3Bi5 present promising platforms for studying kagome superconductivity, band topology, and charge orders in parallel with AV3Sb5. In this work, we comprehensively analyze various properties of ATi3Bi5 covering superconductivity under pressure and doping, band topology under pressure, thermal conductivity, heat capacity, electrical resistance, and spin Hall conductivity (SHC) using first-principles calculations. Calculated superconducting transition temperature (Tc) of CsTi3Bi5 and RbTi3Bi5 at ambient pressure are about 1.85 and 1.92 K. When subject to pressure, Tc of CsTi3Bi5 exhibits a special valley and dome shape, which arises from quasi-two-dimensional compression to three-dimensional isotropic compression within the context of an overall decreasing trend. Furthermore, Tc of RbTi3Bi5 can be effectively enhanced up to 3.09 K by tuning the kagome van Hove singularities (VHSs) and flat band through doping. Pressures can also induce abundant topological surface states at the Fermi energy (EF) and tune VHSs across EF. Additionally, our transport calculations are in excellent agreement with recent experiments, confirming the absence of charge density wave. Notably, SHC of CsTi3Bi5 can reach up to 226ℏ ·(e· Ω ·cm)-1 at EF. Our work provides a timely and detailed analysis of the rich physical properties for ATi3Bi5, offering valuable insights for further experimental verifications and investigations in this field.